Keputusan Pembelian Emosional Pelanggan Beretnis Bugis di Kota Makassar, Indonesia - Karim, Kasnaeny (JSSHA ADPERTISI JOURNAL, 2023)
The Bugis are known as accomplished sailors, who really consider any conditions they will face before carrying out their activities. However, if it is related to consumption patterns, there has been a shift in values, where the visible phenomenon is that this shopping center is never empty even on weekdays or on religious holidays, it is always full of visitors. This behavior can illustrate that currently Bugis consumers make shopping centers a place of activity and Bugis consumer behavior is included in the emotional (hedonic) type, but has not yet answered this phenomenon. Thus, this study aims to explore whether the buying behavior of the Bugis community includes emotional buying behavior when shopping at the mall. This study uses a qualitative approach, which aims to explore the true meaning of the reasons behind the buying behavior of Bugis customers. Research informants obtained by purposive sampling technique. The results of the study show that the motive behind buying behavior at the mall in Makassar city is the existence of an emotional buying motive in shopping caused by (1). The mall is a suitable place for the customer's social status (2) the desire to find a relaxed and comfortable atmosphere, (2). desire for refreshment and recreation with family, (3). Want to spend time at the mall while paying attention to the latest clothing trends worn by other visitors, and (5) desire to socialize while doing business or looking for a side job.